New Essays on Paretos Economic Theory. - Bruni, Luigino (Routledge Studies in the History of Economics, 97., 2009)
This collection brings together major Pareto scholars who examined the various aspects of Paretos thinking, from the point of view both of the history of economics and economic theory.